Rational design of a neutral pH functional and stable organic photocathode. Issue 45 (18th May 2018) - Francàs, Laia; Burns, Eric; Steier, Ludmilla; Cha, Hyojung; Solà-Hernández, Lluís; Li, Xiaoe; Shakya Tuladhar, Pabitra; Bofill, Roger; García-Antón, Jordi; Sala, Xavier; Durrant, James R.
Abstract : Rational design and preparation of an organic photocathode which produces hydrogen for more than 5 hours under 0 V RHE and one sun. Abstract : In this work we lay out design guidelines for catalytically more efficient organic photocathodes achieving stable hydrogen production in neutral pH. We propose an organic photocathode architecture employing a NiO hole selective layer, a PCDTBT:PCBM bulk heterojunction, a compact TiO2 electron selective contact and a RuO2 nanoparticle catalyst. The role of each layer is discussed in terms of durability and function. With this strategically designed organic photocathode we obtain stable photocurrent densities for over 5 h and discuss routes for further performance improvement.